Analisis Pengaruh Aplikasi TikTok terhadap Literasi Digital dan Civic Knowledge Generasi Z - Anggraini, Heny; Sofyan, Fitri Silvia; Nugraha, Yogi (Journal of Civic Education, 2025)
This research aims to analyze the influence of the widely-used TikTok application among Generation Z on digital literacy and its subsequent impact on increasing civic knowledge. The phenomenon of increasing reliance on this short-video platform raises questions about its effects on Gen Z's attitudes and learning habits. Utilizing a quantitative survey method, data was collected via questionnaires distributed to a Generation Z student sample at Universitas Buana Perjuangan Karawang. Descriptive statistical analysis revealed that the use of the TikTok Application (X) has a very strong influence (84.3%) on Digital Literacy (Y1). However, the influence of TikTok use (X) on increasing Civic Knowledge (Y2) was found to be less strong, measuring only 36.5%. These findings suggest that while TikTok is highly effective in boosting Generation Z's digital literacy skills, its direct correlation with the acquisition of substantive civic knowledge remains limited.